2018
DOI: 10.1007/s11469-018-9939-z
|View full text |Cite
|
Sign up to set email alerts
|

Personality Factors in Exercise Addiction: A Pilot Study Exploring the Role of Narcissism, Extraversion, and Agreeableness

Abstract: Despite the increased evidence and acceptance of exercise being classed as a behavioral addiction, there is limited research examining personality characteristics within exercise addicts. The purpose of this study was to examine three personality traits (narcissism, extraversion, and agreeableness) and to examine their role in exercise addiction. The sample comprised 114 voluntary participants (74 females and 40 males) who completed the (i) Exercise Addiction Inventory, (ii) Narcissistic Personality Inventory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Some personality traits have been invoked as potential risk factors for exercise dependence, including extraversion, narcissism, and neuroticism (Bircher et al, 2017;Cook et al, 2020;Costa & Oliva, 2012;Di Lodovico et al, 2018;Lichtenstein et al, 2014).…”
Section: Personality Traits As Risk Factorsmentioning
confidence: 99%
“…Some personality traits have been invoked as potential risk factors for exercise dependence, including extraversion, narcissism, and neuroticism (Bircher et al, 2017;Cook et al, 2020;Costa & Oliva, 2012;Di Lodovico et al, 2018;Lichtenstein et al, 2014).…”
Section: Personality Traits As Risk Factorsmentioning
confidence: 99%
“…Cognitively, impulsiveness is characterized by the absence of reflexive control and the anticipation of posterior consequences, which leads to the making of mistakes in performance situations (Dalley et al, 2011; Smith et al, 2016). Emotionally, impulsiveness is characterized by a low tolerance for frustration, inability to delay reinforcements, little resistance to temptation and few control resources for regulating the impulses to quickly respond (Bridgett et al, 2015; Guinote, 2017), which is in opposition to the qualitative reactions of anger, happiness, anxiety, euphoria, or fear (neurotic response) (Cook et al, 2018). Socially, impulsiveness has been linked with socialization difficulties (Van Stekelenburg and Klandermans, 2017), low empathy (Baldner et al, 2015), prosociality (Do et al, 2017), dependence relations (Odacı and Çelik, 2016), aggressiveness (Johnson and Carver, 2016), and manipulation (Salekin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In sports, functional impulsiveness requires the presence of high concentration (Kovářová and Kovář, 2010; Gustavson et al, 2014) and adequate self-regulation skills to achieve greater efficiency and speed in decision making or emotional expression (González-Hernández and Garcés de Los Fayos, 2014; Laborde and Allen, 2016; Cook et al, 2018). For example, for a taekwondo fighter to make the final attack to close the fight, for a golfer to decide the most appropriate blow on the next hole, or for a tennis player to deal with a disputed point, they need to maintain a high level of activation, which they have previously developed and processed as automatism in their execution of psychological training.…”
Section: Introductionmentioning
confidence: 99%
“…As with the last of the three indicators for EA -the number of hours spent training -the literature indicated that the athletes who trained more had higher EAI scores (Sicilia and González-Cutre, 2011;Szabo et al, 2013b;Latorre et al, 2016;Lukács et al, 2019;González-Hernández et al, 2019b). Besides this, if signs of narcissism and Machiavellianism increase, perseverance efforts grow too, and the likelihood of EA increases considerably, as similar studies have pointed out in the past (Spano, 2001;Lichtenstein et al, 2014;Miller and Mesagno, 2014;Bircher et al, 2017;Cook et al, 2018). Because of this, a narcissistic personality is often described as a pattern of characteristics present in neurotic and obsessive behavior according to the need to improve and excel when evaluated by others (Wallace and Baumeister, 2002) in the search for achieving any objective and performance.…”
Section: Discussionmentioning
confidence: 90%
“…Among all studies into EA, there is a line of research that is focused on the study of personality traits that increase the predisposition of addictive behaviors toward physical exercise linked with characteristics like big five general factors (Andreassen et al, 2013), perfectionism (Bircher et al, 2017), narcissism (Cook et al, 2018), or neuroticism (Lichtenstein et al, 2017). These studies confirmed the direct and combined role of the personality traits as predictive or mediator factors in the development of EA (Bruno et al, 2014).…”
Section: Introductionmentioning
confidence: 78%